2010
DOI: 10.1088/0022-3727/43/8/085403
|View full text |Cite
|
Sign up to set email alerts
|

The local structure of transition metal doped semiconducting boron carbides

Abstract: Brand, Jennifer I.; and Dowben, Peter A., "The local structure of transition metal doped semiconducting boron carbides" (2010 Abstract Transition metal doped boron carbides produced by plasma enhanced chemical vapour deposition of orthocarborane (closo-1,2-C 2 B 10 H 12 ) and 3d metal metallocenes were investigated by performing K-edge extended x-ray absorption fine structure and x-ray absorption near edge structure measurements. The 3d transition metal atom occupies one of the icosahedral boron or carbon atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 39 publications
5
31
0
Order By: Relevance
“…1, and more extensively seen in the supplementary material. The experimentally determined separation between paired Fe ions was about 5.03 ± 0.03 Å [32,37] while the Mn-Mn separation was found to be close to 5.15 ± 0.03 Å [32], and that between Co-Co was found to be about 5.28 ± 0.02 Å [32,36,39]. We found that this model (Fig.…”
Section: Theoretical Methodologymentioning
confidence: 63%
See 3 more Smart Citations
“…1, and more extensively seen in the supplementary material. The experimentally determined separation between paired Fe ions was about 5.03 ± 0.03 Å [32,37] while the Mn-Mn separation was found to be close to 5.15 ± 0.03 Å [32], and that between Co-Co was found to be about 5.28 ± 0.02 Å [32,36,39]. We found that this model (Fig.…”
Section: Theoretical Methodologymentioning
confidence: 63%
“…This understanding of the structure of boron carbides has been obtained from the analysis of experimental extended X-ray absorption fine structure (EXAFS) [32,36,37,39] and near edge X-ray adsorption fine structure [36,39]. The analysis providing the best fit of the unfiltered EXAFS data, even with doping levels of 50-200 ppm, is consistent with a model that has the transition metal Co [32,36,39], Mn [32] or Fe [32,37] atoms preferentially occupying positions in two adjoined icosahedral cages at the apical sites, likely at a boron or carbon site for each cage, as schematically shown in Fig. 1, and more extensively seen in the supplementary material.…”
Section: Theoretical Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Chromium is in many respects very similar, able to adopt a number of nominal valencies from zero valent chromium to chromium þ6 (i.e. [14,15], with very different consequences [15]. It is also known that the electronic properties of lithium borates may be manipulated by the direct inclusion of dopants, as well as, by the presence of Li þ , O, and dopant vacancies to serve as trap sites [10,16].…”
Section: Introductionmentioning
confidence: 99%